Project-Based Learning in Teaching Adsorption Isotherm: The Implementation and Students’ Opinion - Pamenang, Fransisca Ditawati Nur; Wibowo, Rikhardus Sani; Marlinda, Felisitas Bety (Jurnal Penelitian Pendidikan IPA, 2024)
Project Based Learning is one of the learning models that can be chosen by lecturers in learning activities. This learning model is applied in surface chemistry learning, especially on the topic of the adsorption isotherm models. This research aims to find out more about implementation and students’ opinions in project-based learning models. This study employs a mixed-method research approach, utilizing both questionnaires and documentation as data collection methods. The questionnaire instrument consisted of an open and closed questionnaire for the respondents. An open and closed questionnaire was used to collect respondents’ descriptive data on the perception of the model. The project-based learning model received a positive response from students. This positive feedback encompasses interactions with the lecturer, motivation to learn, comprehension of the material, and the execution of project-based learning. This model recognized for its capacity to foster profound comprehension of subject matter, cultivate advanced cognitive skills, and stimulate learners’ intrinsic motivation, serves as an effective approach to enhance student learning experiences.